Frontiers in fertility: a review of breakthroughs in assisted reproductive technology - Vijay, Asha S.; Syed, Fyzullah; Karri, Suresh Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Assisted reproductive technology (ART) is undergoing a transformation driven by emerging biomedical innovations. This review examines recent advances including modulation of the endometrial microbiome, non-invasive preimplantation genetic testing (niPGT) (usually referred as NIPT - non-invasive prenatal genetic testing), mitochondrial replacement therapy (MRT), and reproductive tissue engineering and evaluates their clinical efficacy, ethical implications, and impact on reproductive outcomes. For instance, niPGT has demonstrated up to 80% concordance with invasive testing and reducing biopsy-associated risks. Endometrial microbiota profiling is increasingly used to personalize embryo transfer timing, improving implantation up to 30% of previously unsuccessful in vitro fertilization (IVF) cycles. Innovations in ovarian tissue cryopreservation and 3D bioprinting of reproductive tissues offer fertility solutions for patients with cancer or congenital anomalies. However, these advancements in technology raise ethical concerns around embryo manipulation, germline modification, and equitable access. By synthesizing recent findings, this paper outlines the future trajectory of ART, emphasizing the need for evidence-based integration and regulatory oversight.